"You Can Learn Merely by Listening to the Way a Patient Walks through the Door": The Transmission of Sensory Medical Knowledge. (21st May 2017) - Hammer, Gili
Abstract: Examining the mechanisms of medical knowledge transfer, this article addresses the ways nonvisual senses are employed within medical training, asking about the role of sound, touch, and movement in transmitting knowledge of the body. Based on a 10‐month ethnography in a medical massage training course for blind students, the article examines the ways sensory medical knowledge is transferred in this setting. I discuss the multisensory characteristics of medical knowledge transfer, and the dual process inherent in this sensory pedagogy, in which senses such as touch and hearing undergo medicalization and scientification, while medicine enters the realm of the sensorial. Contributing to emerging research of nonvisual senses in medical training, this case study allows rethinking larger processes of medical knowing, challenging the dominancy of vision as the means of scientific knowledge transmission, and exposing the multisensorial elements of medical perception, and learning in general.